The Influence of Movie Spoilers on Social Media Instagram Towards the Decision to Watch South Korean Drama Shows: Study on SMA Negeri 42 Jakarta - Arniza Devita Putri; Dalilah Adani (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of spoiler impressions on social media Instagram on the decision to watch South Korean drama (K-drama). Korean drama is one form of the entertainment industry that is in great demand by generation Z around the world, including Indonesia. The Korean wave phenomenon is spread massively through social media. The information about the latest K-drama shows is disseminated through spoiler on Instagram. The uses and gratifications theory is the main theory used in this study. This study using a quantitative approach to a casualty with a survey method. The total population of 888 students and a sample of 276 students were obtained based on the Slovin formula with a stratified random sampling technique. The data were collected by questionnaire with a Likert scale. The data were analyzed using the SPSS-24 version and simple linear regression analysis. The result of this study indicates the influence effect of spoiler on Instagram on the decision to watch K-dramas significantly.